DIGITAL AND AUDIO DICTIONARIES IN ENGLISH AND UZBEK LEXICOGRAPHIC PRACTICE - Qayumova Dilobar (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotation. Digital and audio dictionaries have become an essential part of contemporary lexicographic practice in both English and Uzbek languages. This article examines the development, functions, and practical significance of digital and audio dictionaries in modern language learning, translation, and intercultural communication. The study analyzes the integration of multimedia technologies, audio pronunciation models, phonetic transcription systems, and corpus-based lexicographic approaches within English and Uzbek dictionary resources. Special attention is devoted to bilingual digital dictionaries, mobile applications, and online platforms that provide interactive learning opportunities, contextual examples, and native-speaker audio recordings. The research highlights the challenges of lexical equivalence, idiomatic translation, and pronunciation accuracy between English and Uzbek, while also emphasizing the growing role of user-centered design and digital accessibility in lexicographic practice. The findings demonstrate that digital and audio dictionaries significantly improve vocabulary acquisition, pronunciation skills, listening comprehension, and independent language learning, making them indispensable tools for modern linguistic education and communication.
Keywords: Keywords: digital dictionaries; audio dictionaries; lexicography; English lexicography; Uzbek lexicography; bilingual dictionaries; phonetics; pronunciation; language learning; corpus linguistics.